Fundamental mechanisms and their interactions in shear‐clinching technology and investigation of the process robustness - Wiesenmayer, Sebastian; Han, D.; Müller, Manuel; Hoerhold, R.; Meschut, G.; Merklein, Marion (Materialwissenschaft und Werkstofftechnik, 2019)
The compliance with increasingly stricter emission standards is a challenge for the automotive industry, which requires the utilization of lightweight materials e. g. aluminium and high-strength steels. Hereby, the load-optimized design of body parts and the reduction of wall thicknesses are enabled. But, due to the use of dissimilar materials, common joining technologies are reaching their limits. On the one hand, joining by welding is often not possible because of different melting temperatures. On the other hand, joining by forming with additional fasteners increases the cycle time and the costs. However, joining by forming without fasteners is often limited by the mechanical properties of the joining partners. The innovative shear-clinching technology combines shear-cutting and clinching in a single stage process and thereby enables joining by forming of materials with high differences regarding their mechanical properties. However, by the combination of the sub-processes cutting and joining, the complexity of the technology is increased. Thus, within the scope of this work, the fundamental mechanisms in shear-clinching and their interactions as well as the robustness of the process are analysed, in order to promote the applicability of the technology.
CRIS-Team WoS Importer:2019-08-09